Top Seven Reasons to Celebrate and Ask More from Labour/Le Travail - Roediger, David (Labour/Le Travailleur, 2002)
Abstract Tribute to, and assessment of, the first 49 issues of Labour/Le Travail concentrates on both the tone and the substance of the journal. The seven sections of the article discuss matters ranging from art and design, to the rich poetry long included in its pages, to the ability to publish articles that are at once politically informed and academically rigorous. The evolution of the wide-ranging and exemplary book review section and the long standing attention of L/LT to racial and gender divisions among working people receive attention, as does a brief comparison of the trajectory of L/LT with that of Labor History in the United States. A final section considers the necessity for free wheeling debate among labour historians, particularly over the question of class and the place of Marxism in our work.